IMPLEMENTATION OF GREEN SUPPLY CHAIN MANAGEMENT AND MITIGATION STRATEGY FOR HALAL FOOD MANAGEMENT SUPPLY CHAIN - Kuncorosidi Kuncorosidi; Iqlima Achzany Mugies (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2022)
Industrial estates are usually reflected in the existence of a certain standardization. The green industrial area was born with Green Supply Chain Management. The halal industry gave birth to Halal supply chain management. So far, there has not been an application of an environmentally friendly concept in the halal industrial area that applies the concept of Halal supply chain management. The concept of Halal supply chain management should complement the existing concepts. This is what the researchers then found a middle way to do by continuing to carry out Halal Supply Chain Management which is also environmentally friendly. This research is a literature study by examining the quality of the study, the process of collecting and sorting data according to the intended object, data analysis, interpretation of the results, and recommendations of the research results. The results of the analysis show that Halal is reflected in Halal Supply Chain Management, while Green Supply Chain Management reflects “thoyy?b?n” (good) in the environment. The two concepts basically become one unit in "h?lal?n thoyy?b?n". So that the results of research with the implementation of environmentally friendly concepts in the supply chain of the halal industry have an additional positive impact in three aspects, namely. Financial, Environmental, and Social. r. A mitigation strategy is prepared by involving the government, suppliers, companies, and distributors. The formulation of a mitigation strategy is focused on the aspects of technology, human resources, and infrastructure. Keywords: risk assessment, mitigation strategy, halal, supply